Analisis Kebutuhan Pengembangan E-Modul Fisika untuk Meningkatkan Kemampuan Berpikir Kritis dan Literasi Sains di SMA - Yunita Syafitri; Syafriani (Postgraduate, University of Mataram, 2023)
The purpose of this study was to analyze the needs of development of physics e-module integrated with critical reading. Development using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This is descriptive qualitative research with questionnaire and interview methods. The data were analyzed using descriptive descriptively with the results of data processing in percent (%). The result showed that 86 % of physics teacher use the textbooks for teaching materials and 65.14 % of student’s thinking skills still in the low categories. Furthermore, the results also showed that 62.13 % of students have no interest in reading. It can be concluded that the development of physics e-module not only can be improving student’s critical thinking but also student’s scientific literacy.